Asset allocation and risk taking under different interest rate regimes - Lieven Hermans; Thomas Kostka; Danilo Vassallo (European Central Bank (ECB), 2023)
We study the effects of low short-term interest rates on the optimal portfolio allocation in Markowitz portfolios and Risk parity portfolios. We propose a measure of Portfolio Instability, gauging the amount of optimal portfolio shifts needed to respond to exogenous shocks to the expected risk and return of the risky portfolio assets. Portfolio Instability, i.e. the selling pressure on riskier asset holdings, is found to be stronger the lower the risk-free interest rate. Heightened portfolio instability in the presence of low rates is found to emerge through two channels both of which incentivise the build-up of large and leveraged risky asset shares during calm periods which need to be unwound in the event of higher market volatility: first, low rates (mechanically) augment the excess return to be gained by investing in riskier assets and second, they are found to dampen volatility of riskier assets in the portfolio. The inverse relationship between portfolio instability and the risk-free rates is found to increase the closer the risk-free rate approaches the effective lower bound. Counterfactual analyses of the behaviour of optimal multi-asset portfolios demonstrate that the sell-off in riskier asset classes during the Covid crisis in March 2020 was more severe than would have been in the presence of higher short-term interest rates.
Keywords: C58; E52; G11; G12; 330; CAPM; Counterfactual analysis; portfolio optimization